Short Communication: Phytohormone Quantification of Kappaphycus alvarezii at Different Cultivated Ages - Cokrowati, Nunik; Risjani, Yenny; Andayani, Sri; Firdaus, Muhammad (Jurnal Perikanan dan Kelautan, 2023)
Kappaphycus alvarezii is used in industry as a food ingredient, a source of hydrocolloids, cosmetics, food additives, animal feed, fertilizers, biofuels, and medicinal ingredients. K.alvarezii is cultivated in several areas in Indonesia, including on the island of Lombok. The production of K.alvarezii is related to its growth and it is related to its phytohormones. K.alvarezii cultivated in Lombok is currently not known for its composition and amount of phytohormones. The content of phytohormones at different planting ages is of course different. The purpose of this study was to determine the number of phytohormones in seaweed K. alvarezii at different planting ages. This study was conducted in Ekas Bay, Lombok, Nusa Tenggara Barat from June to December 2020. The study used experimental methods and descriptive data analysis. The results of this study explain that currently cultivated K. alvarezii contains cytokinins, auxins, and gibberellins. Cytokinins obtained on the 9th day of planting were 11.62 ppm and increased on the 18th day to 12.34 ppm. At the next planting age, it continued to decrease on the 27th day to 11.43 ppm and at harvest time, the 45th day of 10.69 ppm. Auxin detected in the seeds used was 644.93 ppm, on the 27th day of 14.27 ppm, on the 36th day of 1078.25 ppm. Giberilin was detected on the 9th day at 0.49 ppm. This study concluded that K. alvarezii at different planting ages had different phytohormones content.